A Language for Stating Component Quality - Burgués, Xavier; Franch, Xavier (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2000.25921, 2000)
We present in this paper a language for stating component quality in the framework of the ISO/IEC quality standards. The language consists of three different parts. In the first one, software quality characteristics and attributes are defined, probably in a hierarchical manner. As part of this definition, abstract quality models can be formulated and further refined into more specialised ones. In the second part, values are assigned to component quality basic attributes. In the third one, quality requirements can be stated over components, both context-free (universal quality properties) and context-dependent (quality properties for a given framework software domain, company, project, etc). Software Components may be then selected by testing whether their behaviour with respect to the quality characteristic satisfy some quality requirements that model the context of selection. This gives some potential benefits in the software selection framework. We show how the language can be used through some examples.